Economic sociology : an introduction - Hass, Jeffrey Kenneth (Routledge, 2007)
Providing a comprehensive overview of economic organisation and practice in developed and developing countries, this text also systematises insights of economic sociology, and contrasts it with economic theory, to show accomplishments as well as weaknesses and work remaining.